Virus infections: escape, resistance, and counterattack. - Xu, X; Screaton, G; Mcmichael, A (2001)
Many viruses establish life-long infections in their natural host with few if any clinical manifestations. The relationship between virus and host is a dynamic process in which the virus has evolved the means to coexist by reducing its visibility, while the host immune system attempts to suppress and eliminate infection without damage to itself. This short review describes a variety of strategies that are employed by viruses to evade host immune responses. These include virus-associated escape from T cell recognition, and resistance to apoptosis and counterattack, with special reference to two papers published in this issue of Immunity (Mueller et al., 2001; Raftery et al., 2001).